Detection of rupture inside rubber bearings using active sensing method. (15th November 2022) - Zeng, Yi; Wang, Haishen; Deng, Kailai; Pan, Peng
Highlights: An active sensing method and the linear discriminant analysis (LDA) method is proposed to detect the rubber rupture inside the rubber bearing. The LDA method can comprehensively take into account the influence of axial pressure and shear deformation, with 98% accuracy for the rubber rupture damage detection. The LDA method also has the superior performance in detecting the degree of rupture damage, the accuracy is 95.8%. Abstract: Rubber bearings are key components of base-isolated structures; therefore, it is important to monitor their damage states. This study investigates the effectiveness of the active sensing method for detecting rubber rupture inside rubber bearings. The mechanism of wave propagation demonstrates the potential of the active sensing method for rubber rupture damage detection. Detection tests were performed on a full-scale rubber bearing, and a swept signal from 1 kHz to 100 kHz was used as the detection signal. A linear discriminant analysis (LDA) method based on the wavelet-packet energy spectrum is proposed to detect the rubber rupture damage. The LDA method can comprehensively consider the influences of axial pressure and shear deformation, displaying a 98% accuracy for rubber rupture damage detection. In addition, detection tests were performed on a scaled rubber specimen under different damage states. The results show that the LDA method has excellent performance when detecting the degree of rupture damage, with an accuracy of 95.8%.